solve by cramers rule
Attachments:
![](https://hi-static.z-dn.net/files/db5/af8b41bb9f62255383d3e8e1151c363e.jpg)
Answers
Answered by
4
x+y-7/3=2x-y+1/5
5(x+y-7)=3(2x-y+1)
=5x+5y-35=6x-3y+3
=5x-6x+5y+3y=3+35
=-x+8y=38....(1)
x+y-7/3=3x+y-11/7
7(x+y-7)=3(3x+y-11)
7x-9x+7y-3y=-33+49
-2x+4y=16
-x+2y=8....(2)
by Cramer rule is as following upper.
mark my answer as brainliest.
Attachments:
![](https://hi-static.z-dn.net/files/dae/b56ae23ed2e50e98afd7eb5acfc38c14.jpg)
![](https://hi-static.z-dn.net/files/da0/043ad4555d63609c7a682ddd527f1a8c.jpg)
siddhi4372:
thanks a lot
Similar questions